Pertumbuhan dan Hasil 17 Genotipe Melon (Cucumis melo L.) di dataran rendah Bengkulu Utara : Pertumbuhan dan Hasil 17 Genotipe Melon (Cucumis melo L.) di Dataran Rendah Bengkulu Utara - Togatorop, Eny; Abdilah, Willi; Parwito; Sari, Dia Novita; Saputra, Helfi Eka (PendIPA Journal of Science Education, 2025)
National melon production has decreased from 2021 to 2023. One means to overcome this decline is through the expansion of planting areas. The potential of lowland areas can be optimized to enhance melon production. The development of melon varieties in lowlands relies heavily on the availability of germplasm. Genetic diversity within germplasm is a key prerequisite for producing adaptive and high yielding varieties. This research aims to identify melon genotypes with optimal growth and yield performance in lowland areas. The study was conducted at the Arga Makmur experimental farm, North Bengkulu Regency, from January to March 2024, at an altitude of 203.9 meters above sea level. The experiment used a single-factor Randomized Complete Block Design (RCBD) with 17 melon genotypes as treatments and three replications. Data were statistically analyzed using the F-test, and significant genotypic treatments were further evaluated using the Duncan Multiple Range Test at a 5% significance level. The results identified five selected melon genotypes based on high fruit weight, fruit diameter, and sweetness level: genotypes G3, G4, G7, G12, and G17.